Cholera in selected countries in Asia. (29th February 2020) - Lopez, Anna Lena; Dutta, Shanta; Qadri, Firdausi; Sovann, Ly; Pandey, Basu Dev; Bin Hamzah, Wan Mansor; Memon, Iqbal; Iamsirithaworn, Sopon; Dang, Duc Anh; Chowdhury, Fahima; Heng, Seng; Kanungo, Suman; et al.
Abstract: Introduction: Although the current pandemic of cholera originated in Asia, reports of cholera cases and outbreaks in the region are sparse. To provide a sub-regional assessment of cholera in South and Southeast Asia, we collated published and unpublished data from existing surveillance systems from Bangladesh, Cambodia, India, Malaysia, Nepal, Pakistan, Philippines, Thailand and Vietnam. Methods: Data from existing country surveillance systems on diarrhea, acute watery diarrhea, suspected cholera and/or confirmed cholera in nine selected Asian countries (Bangladesh, Cambodia, India, Malaysia, Nepal, Pakistan, Philippines, Thailand and Vietnam) from 2011 to 2015 (or 2016, when available) were collated. We reviewed annual cholera reports from WHO and searched PubMed and/or ProMED to complement data, where information is not completely available. Results: From 2011 to 2016, confirmed cholera cases were identified in at least one year of the 5- or 6-year period in the countries included. Surveillance for cholera exists in most countries, but cases are not always reported. India reported the most number of confirmed cases with a mean of 5964 cases annually. The mean number of cases per year in the Philippines, Pakistan, Bangladesh, Malaysia, Nepal and Thailand were 760, 592, 285, 264, 148 and 88, respectively. Cambodia and Vietnam reported 51 and 3 confirmed cholera cases in 2011, with no subsequent reported cases. Discussion and conclusion: We present consolidated results of available surveillance in nine Asian countries and supplemented these with publication searches. There is paucity of readily accessible data on cholera in these countries. We highlight the continuing existence of the disease even in areas with improved sanitation and access to safe drinking water. Continued vigilance and improved surveillance in countries should be strongly encouraged.